Ocorrência de opacidade de cápsula posterior em cães pós-facoemulsificação, com ou sem a utilização de lente intraocular dobrável e efeitos do Nd: Yag Laser - Conceição, Luciano Fernandes da [UNESP] (2014)
Cataracts are among the most common eye diseases in dogs, being the phacoemulsification method the one that best suits in their therapy. The posterior capsule opacification (PCOs) are among the most common complications and manifest themselves in weeks or months after cataract surgery. Intraocular lenses (IOLs) used in the correction of postoperative hyperopia, are mentioned as useful in the prevention of PCOs , especially the foldable acrylic ones with truncated or square edges. However, when PCOs are set up, capsulotomies are required as a treatment. In human patients, the effects of the Nd:YAG laser are recognized as a noninvasive and secure technique against such problems. To compare the results of eyes of dogs that received foldable acrylic intraocular lenses with eyes of aphakic dogs, after phacoemulsification, during a period of 180 days it was used 20 dogs of several breeds, male or female , ranging from 3 to 7 years old , with juvenile, immature or mature (n = 10 immature, mature n = 10) bilateral cataracts . Two groups (G1 = with implantation of intraocular lens and G2 = no artificial lens implant) were randomly formed and all dogs had both eyes operated. After the surgery, the patients were weekly evaluated for the presence or absence of synechiae, discoria, intraocular pressure, uveal inflammation and presence or absence of posterior capsule opacification during a period of 180 days. At 60, 90, 120, 150 and 180 days after surgery, the posterior capsule images were captured for evaluation of their opacity. Eyes with score 2 or 3 of opacity were underwent to capsulotomy by Nd:YAG laser. Ordinal categorical variables were compared (G1 X G2) using the chi-square and Fisher´s exact test. Quantitative variables were compared using ANOVA with Tukey post test. Synechiae were observed in the same frequency in both groups .G2 showed 30 % more discoria when compared to G1 Intraocular pressure did not differ between the groups. The ...